2013
DOI: 10.1038/srep01173
|View full text |Cite
|
Sign up to set email alerts
|

A simple medium enables bovine embryos to be held for seven days at 4°C

Abstract: Cryopreservation methods using liquid nitrogen (LN2) for gametes and embryos are prevalent in mammalian artificial reproduction. However, the pregnancy rate from frozen embryos has not improved over the past two decades because freeze–thawing causes significant damage. The strict regulation of transportation of LN2 containers by airlines also limits exchange between breeders. In this article, we introduce a medium that enabled bovine embryos to be held for up to 7 days at 4°C. A pregnancy rate of 75% (24/32) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 38 publications
2
33
1
Order By: Relevance
“…In both experiments, blastocysts produced from oocytes matured in a medium containing 800 pg/ml of ghrelin appeared to be of better quality in comparison with their counterparts, as the hatching rate – used as a quality marker (Ideta et al. ) – was significantly increased. Serum was present in our embryo production system.…”
Section: Discussionmentioning
confidence: 90%
“…In both experiments, blastocysts produced from oocytes matured in a medium containing 800 pg/ml of ghrelin appeared to be of better quality in comparison with their counterparts, as the hatching rate – used as a quality marker (Ideta et al. ) – was significantly increased. Serum was present in our embryo production system.…”
Section: Discussionmentioning
confidence: 90%
“…Ideta et al () reported that the addition of serum with a high concentration in the storage medium enhances viability of bovine embryos after hypothermic preservation compared with BSA addition. They suggested that bovine embryos could be stored in 100% bovine serum at hypothermic temperatures (Ideta et al, ). Serum provides energy substrates and amino acids for metabolic and anabolic processes as well as chelation of heavy metal ions or other toxins (Shah, ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, serum supplementation during the hypothermic storage of bovine embryos was reported to maintain their viability (Ideta et al . ). Furthermore, supplementing a basic holding medium with serum was reported to maintain the viability of immature porcine oocytes preserved under ambient temperatures (Yang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Under hypothermic conditions serum also seems to act positively on the viability of bovine embryos (Ideta et al . ). Antioxidants such as α‐tocopherol, cysteamine, cysteine (Wang et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation